SISTEM PENENTUAN KELAYAKAN PEMBERIAN SUSU FORMULA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN ELECTRE - Yunita Rahma; Sufiatul Maryana; Benny Nofika (STMIK KAPUTAMA, 2021)
Breastmilk (ASI) is the baby's first food. According to WHO, ASI is the best source of nutrition for babies and toddlers. However, not all mothers can breastfeed their babies well. Stopping breastfeeding or even not being given ASI at all can occur for various reasons, for example, the baby's mother is suffering from an infectious disease and it is feared that it will spread to the baby if the baby drinks the mother's milk or the baby's mother is consuming drugs that are quite dangerous. Providing formula milk is an alternative solution to fulfill the baby's nutrition because its content is deemed sufficient to fulfill the baby's nutrition. Seeing the problem, This research, this research offers a solution to determine the feasibility of giving formula milk by making a decision support system with the SAW (Simple Additive Weighting) and Electre methods. The alternatives used by the SAW method consist of 5 alternatives, the Electre method process conducts an assessment by giving a range to the alternative value input. The study obtained results by entering alternative data as many as 5 names of breastfeeding mothers who had doubts in determining whether to use formula milk or not. From the 5 names, Suhartini was chosen as an alternative.